Linear Widths of the Besov Classes of Periodic Functions of Many Variables. II - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain order estimates for linear widths of the Besov classes \(B_p,θ ^r\) of periodic functions of many variables in the space L q for certain values of parameters p and q different from those considered in the first part of the work.